Real‐Time NMR Monitoring of Spatially Segregated Enzymatic Reactions in Multilayered Hydrogel Assemblies. Issue 35 (19th July 2021) - Nordin, Nurdiana; Bordonali, Lorenzo; Davoodi, Hossein; Ratnawati, Novindi Dwi; Gygli, Gudrun; Korvink, Jan G.; Badilita, Vlad; MacKinnon, Neil
Abstract: Compartmentalized chemical reactions at the microscale are important in biotechnology, yet monitoring the molecular content at these small scales is challenging. To address this challenge, we integrate a compact, reconfigurable reaction cell featuring electrochemical functionality with high‐resolution NMR spectroscopy. We demonstrate the operation of this system by monitoring the activity of enzymes immobilized in chemically distinct layers within a multi‐layered chitosan hydrogel assembly. As a benchmark, we observed the parallel activities of urease (Urs), catalase (Cat), and glucose oxidase (GOx) by monitoring reagent and product concentrations in real‐time. Simultaneous monitoring of an independent enzymatic process (Urs) together with a cooperative process (GOx + Cat) was achieved, with chemical conversion modulation of the GOx + Cat process demonstrated by varying the order in which the hydrogel was assembled. Abstract : We integrate a compact, reconfigurable reaction cell featuring electrochemical functionality with high‐resolution NMR spectroscopy. This system is used to monitor the activity of enzymes immobilized in chemically distinct layers within a multi‐layered chitosan hydrogel assembly. We observed the parallel activities of urease, catalase, and glucose oxidase by monitoring reagent and product concentrations in real‐time.